Typification of names in the genus Anaphyllum (Araceae) - M, Sivadasan; V, Abdul Jaleel; Boyce, Peter C; Alfarhan, Ahmed H; El-Sheikh, Mohamed A; Al-Obaid, Sami M (Phytotaxa, 2016)
The little-known and small genus Anaphyllum (Araceae), represented by only two species endemic to India, namely A. beddomei and A. wightii, has remained without correctly designated types. Their syntypes are recognized and the names are here typified. The correct bibliographic reference to the protologue of A. wightii is provided for the first time.